Interactive Tangible User Interface for Early Childhood Education: A Usability Study on Teaching Geometric Shapes in Kindergarten - Muhamad Yusvin Mustar; Rudy Hartanto; Paulus Insap Santosa, (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Tangible user interfaces (TUIs) offer significant educational benefits, but their use in kindergarten, particularly for teaching geometric shapes, remains underexplored, with research largely focused on elementary education or higher levels. Moreover, usability evaluations assessing the ease of use of such tools by teachers as end-users are rarely conducted. This study aims to address these gaps by designing and evaluating TUI interactive surfaces as an aid for teaching geometric shapes in kindergarten. The proposed TUI design was evaluated for usability using the System Usability Scale with kindergarten teachers, achieving a score of 97.43, categorized as ‘Good’ (Grade A). This score indicates superior and acceptable performance, placing it in the highest quartile (4th quartile). Furthermore, functionality testing of the TUI system demonstrated a 100% success rate in its application as a geometric shape learning media. These findings suggest that the proposed TUI design is a viable and effective tool for teaching geometric shapes in kindergarten, offering a practical and user-friendly solution for educators. The study’s limited sample size, subject focus, and lack of teacher diversity affect generalizability, highlighting the need for future research to expand TUI applications, assess long-term impacts, and include diverse teacher demographics.